TEACHER WORK ENGAGEMENT IN INCLUSIVE SCHOOL - Rosyanti, Daisy Marthina; Armanu, Armanu; Ratnawati, Kusuma (Jurnal Aplikasi Manajemen, 2021)
This research aimed to identify and state the significance of teacher work engagement to improve inclusive school performance, where the inclusive school was a form of education equity and realization without any discriminations which currently have been organized by the government of Indonesia. Further, this research was based on the phenomenon which happened that not all teachers in inclusive school were involved maximally on the inclusive concept. This research was categorized into qualitative research which exerted case study approaches to explore the teacher experience during teaching activity in the inclusive school. It aims to identify teacher engagement at work. This research finding showed that the teacher work engagement was affected by self-efficacy and organizational climate. The teacher who had high self-efficacy referred that the teacher believes their selves were able to fulfill daily challenges in the school and therefore, the teacher tended to be more engaged on work. Besides, this research finding, indicated that the fun organizational climate became attendant which could influence the teacher work engagement.